If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 20 = 12x + -68 Reorder the terms: 20 + 4x = 12x + -68 Reorder the terms: 20 + 4x = -68 + 12x Solving 20 + 4x = -68 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 20 + 4x + -12x = -68 + 12x + -12x Combine like terms: 4x + -12x = -8x 20 + -8x = -68 + 12x + -12x Combine like terms: 12x + -12x = 0 20 + -8x = -68 + 0 20 + -8x = -68 Add '-20' to each side of the equation. 20 + -20 + -8x = -68 + -20 Combine like terms: 20 + -20 = 0 0 + -8x = -68 + -20 -8x = -68 + -20 Combine like terms: -68 + -20 = -88 -8x = -88 Divide each side by '-8'. x = 11 Simplifying x = 11
| 16t^2+320t=0 | | -5=6x-5 | | -1-3=x | | 10=2p-2 | | -1-1=x | | 6x+7=70-3x | | -16t^2+320t=h | | 267-7x=38x+17 | | 3-1=x | | -[n-5]=6 | | 8n+n=7n+10 | | 13-9x=59-23x | | 1-6x+4x=-x | | 3x-12=24-x | | 4X^3-27x+27=0 | | 6y-6=4y+16whatsy | | -2(5n+1)=7-n | | -100-9x=8x+19 | | -3(5x+2)=14-5x | | x^2+2x-120=0 | | 1+n=-n-7 | | 7(2b-5)+3=10 | | 3x-6=-2x-1 | | -4+4v=2(v-4) | | -30-4x=12-10x | | -2-4p=-2(p+3) | | 4x^2+kx+49=0 | | 6x+23=13x-61 | | 5x-6=26 | | -3x^2-6x+9=0 | | 3x-12=-24x | | 3x-12=24x |